2017
DOI: 10.3389/fphys.2017.00966
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29a Suppresses Spermatogenic Cell Apoptosis in Testicular Ischemia-Reperfusion Injury by Targeting TRPV4 Channels

Abstract: Background: MicroRNAs (miRNAs) have emerged as gene expression regulators in the progression of ischemia-reperfusion injury (IRI). Accumulating evidences have indicated miR-29a play roles in myocardial and cerebral IRI. However, the role of miR-29a in testicular IRI has not been elucidated.Methods: Changes in expression of miR-29a and Transient Receptor Potential Vanilloid 4 (TRPV4) in animal samples and GC-1 spermatogenic cells were examined. The effects of miR-29a on spermatogenic cell apoptosis in testicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…We also examined the expression of TRPV4 on the protein level by western blot analyses using an anti‐TRPV4 antibody. Figure B shows the expression of a protein of ~ 90 kDa, which is in good agreement with the others reported .…”
Section: Resultssupporting
confidence: 91%
“…We also examined the expression of TRPV4 on the protein level by western blot analyses using an anti‐TRPV4 antibody. Figure B shows the expression of a protein of ~ 90 kDa, which is in good agreement with the others reported .…”
Section: Resultssupporting
confidence: 91%
“…Nine miRNAs (miR-1199-3p, miR-149-5p, miR-217-3p, miR-22-5p, miR-29a-5p, miR-3550, miR-3568, miR-3575, and miR-423-3p) have binding sites with circ003593. Previous studies have showed that miR-29a-5p and miR-423-3p play important role in I/R injury ( Ning et al., 2017 ; Rizzacasa et al., 2019 ). Our analysis found that circ003593 interacted with both miR-29a-5p and miR-423-3p.…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant level of miR-29a has been observed in POF tissues [ 26 ]. miR-29a has been reported to inhibit the apoptosis of various cell types, including cardiomyocytes [ 60 ], vascular endothelial cells [ 61 ], and spermatogenic cells [ 62 ]. In our study, we conducted experiments on the biological effects of human UCMSC-derived exosomes carrying miR-29a and their mechanisms against POI progression.…”
Section: Discussionmentioning
confidence: 99%